Association of rotating shift work with incident irritable bowel syndrome: a large population-based prospective cohort study - Zhong, Yang; Bai, Hao; Zhang, Yuan; Yang, Xiaorong; Zhang, Tongchao; Liu, Xinjie; Li, Zhen; Chen, Hao; Lu, Ming (Frontiers in Public Health, 2025)
ObjectivesLimited epidemiological study has examined the association between rotating shift work and risk of irritable bowel syndrome (IBS). This study aimed to investigate the association between shift work and risk of IBS and explore the potential mediating factors for the association.MethodsA total of 268,290 participants from the UK Biobank were included. Cox proportional hazards model was used to examine the associations between shift work and the incidence of IBS. The mediation analyses were performed to investigate the mediating effects.ResultsParticipants engaged in always/usually shift work showed a significantly increased risk of developing IBS (HR: 1.12, 95% CI: 1.03–1.23). Joint analysis indicated that, participants with both always/usually shift work and inadequate sleep duration had a 54% increased risk of IBS (HR: 1.54, 95% CI: 1.35–1.82) compared to those with adequate sleep duration and never/rarely shift work; while participants with both always/usually shift work and insomnia-always had a 65% increased risk of IBS (HR: 1.65, 95% CI: 1.43–1.90) compared to those with never/rarely shift work and never/sometimes insomnia. Mediation analysis revealed that sleep quality and anxiety/depression partially mediated the relationship between shift work and IBS incidence, contributing 16.1% (6.8–25.4%) and 3.6% (0.4–6.8%) of the mediation effect, respectively.ConclusionThis study found that participants with always/usually shiftwork status had significantly increased risk of IBS, and this association may partially be mediated by anxiety/depression and sleep quality. Moreover, inadequate sleep duration and usually insomnia may intensify the effect of rotating shift work on the risk of incident IBS.